2009
DOI: 10.1016/j.schres.2008.11.023
|View full text |Cite
|
Sign up to set email alerts
|

Obsessive compulsive symptoms in the psychosis prodrome: Correlates of clinical and functional outcome

Abstract: Objectives Obsessive-Compulsive Disorder (OCD) is a common co-morbid condition in schizophrenia, associated with poor prognosis. However, the prevalence of obsessive compulsive symptomatology (OCS) and its relationship to outcome has not been evaluated in adolescents at ultra high-risk for psychosis (UHR). Methods Sixty-four UHR and 26 non-prodromal comparison (NPC) youth were ascertained using the Structured Interview for Prodromal Syndromes (SIPS). Participants completed diagnostic interviews and the Padua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
68
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(83 citation statements)
references
References 22 publications
9
68
2
Order By: Relevance
“…The severity of OC symptoms and degree of functional impairment were not correlated in either sample (Niendam et al, 2009a;Hur et al, 2012). However, seemingly conflicting results were found when patients in these studies were dichotomised into high and low OC symptom groups.…”
Section: Anxietymentioning
confidence: 87%
See 1 more Smart Citation
“…The severity of OC symptoms and degree of functional impairment were not correlated in either sample (Niendam et al, 2009a;Hur et al, 2012). However, seemingly conflicting results were found when patients in these studies were dichotomised into high and low OC symptom groups.…”
Section: Anxietymentioning
confidence: 87%
“…In addition to clinically diagnosable disorders, this population also report high levels of anxiety symptoms (Niendam et al, 2009a;Chudleigh et al, 2011). In the largest cross-sectional study to date, self-reported anxiety symptoms were found to be modestly correlated with global functioning (measured with the GAF) and a single-item measure of role functioning, but not with more detailed measures including the Global Functioning: Social and Role scales (Fulford et al, 2013).…”
Section: Anxietymentioning
confidence: 89%
“…Studies have suggested OCD patients bordering on the psychotic may be the group most responsive to antipsychotic augmentation (Rodowski et al, 2008). Furthermore, there is some evidence to suggest that some early cases of schizophrenia-spectrum disorders may initially present with obsessive-compulsive symptoms, and vice versa (Niendam, Berzak, Cannon & Bearden, 2009;Rodowski et al, 2008;Tumkaya et al, 2009). Therefore, this extreme case of OCD may be the precursor to a future psychotic disorder, which may also account for the responsiveness to risperidone.…”
Section: Risperidonementioning
confidence: 99%
“…OCD-schizophrenia comorbid patients are more likely to have a previous history of suicidal ideation and attempts. Also, OCS severity is associated with suicidality in adolescents at ultra-high risk for psychosis (Niendam et al, 2009;Sevincok et al, 2007).…”
Section: Introductionmentioning
confidence: 99%